منهج الشيخ محمد بن صالح بن عثيمين في الفتوى - محمد رمضان النجار
The research focuses on how to know the methodology of a contemporary scholar in Islam in his verdict. This scholar is known to be Sheikh Mohammad bin Saleh bin Uthaimeen may Allah have mercy upon him- (1 347-1421 h). Indeed, there are great benefits in learning about the methodology of godly scholars in Islam; doing so will enhance and enrich the field of learning research, as well, it will be a directory for the seeker of religious knowledge in order to imitate those scholars. The researcher has searched for the personal and learning life history of this particular aforementioned sheikh bin Uthaimeen. The researcher sifts thoroughly in searching sheikh's books and his verdict. The researcher came out with a research that directly goes to the translations, explanations of what this sheikh has been given of a big position in comparison to the other scholars, talkless of an ordinary man. The researcher also went on by analyzing sheikh's methodologies in using the reference with quran and prophetic traditions with hadith, which is collectively agreed upon by the congregation, or by individuals, also with sheikh's point of view in the weak hadith, and his references to the consensus, measurement's yard stick, intellect and his usage of principle of jurisprudence and technology for valeting religion, his steadfastness to the views of convention of the scholars and his works with obvious quranic verses or hadiths, how he has compiled within the proofs. Moreover, his explanation in turning to the views of denominations, thought of companions of prophets, their followers, school of thoughts, those who deal with clear evidence and people of innovations. Also, how the sheikh compiled the disagreements of Islamic scholars in religious matters, and how he gave a proof for the most soundable one. In addition, the researcher explains sheikh's diligence and dependence in verdict which comprises the researches about diligence, diligent and imitator, by remembering tryness of sheikh in contemporary issues, his concern about issues of muslims and muslim nation, Then talk on verdict, a person eligible to give it and a seeker for it. Till the time of writing these lines, the researcher doesn't find something about methodology of sheikh bin Uthaimeen in verdict. This research has come up with numerous results to mention are: that great position which sheikh has gained at the mist of Muslims. His brilliance, his broad knowledge, and his strength in resolution. Also, the step which sheikh took after the past righteous men of this ummah, his in abnormalities on non deviation from the methodologies and principles of the past righteous servant, his acquaintance with the different denominations, all this give his verdicts more power and result in its adherence and its spread within the muslims. He is a sample godly knowledgeable one, and he is worthy to be followed by others as well.